SIKAP RAMAH LINGKUNGAN SISWA SMP NEGERI 8 SEMARANG MELALUI PELATIHAN HIDROPONIK - Intan Rizky Amalia; Fajrina Asabela Putri; Siti Musapana; Dika Wahyuningrum; Cucianingsih Cucianingsih (UNIVERSITAS PGRI MADIUN, 2019)
The low preservation of the environment makes the atmosphere less cool. One solution to the problem related to environmental preservation is by planting through hydroponics. The aim is to build an environmentally friendly attitude to students of SMP N 8 Semarang and to bring up students' desire to grow crops. Planting in a hydroponic manner in addition to helping preserve the environment, can also be useful to meet food consumption, health, and improve student concentration when the environment is beautiful. The hydroponics training was conducted by the laboratory at SMP N 8 Semarang for 3 days. The purpose of this study was to determine the environmentally friendly attitude of students of SMP Negeri 8 Semarang through hydroponic training. The method used is hydroponic observation training, interviews and questionnaires for students of SMP N 8 Semarang before being given training and after training using a behavioral checklist. The results of the study showed that there was a comparison of scores between before and after, namely the questionnaire before treatment obtained an average of 79.1 and the questionnaire after treatment obtained an average of 91.4. This data means that students care about the environment and students' interest in hydroponics is getting better. This was stated because students had taken the training activities seriously. This article concludes that to preserve the school environment the environment-friendly attitude of students of SMP N 8 Semarang is treated through hydroponic training.